PENGELOLAAN BAHAN BAKAR DALAM RANGKA MENCEGAH KEBAKARAN HUTAN DENGAN METODE SEKAT BAKAR DI KAWASAN KHDTK DIKLAT KEHUTANAN SISIMENI SANAM - Sinaga, Pamona Silvia; Ayu, Priskafila Kurniawati (Jurnal Akar, 2021)
Abstract: Special Purpose Forest Region (SPFR) Sisimeni Sanam is one of the area that often forest fire every year. Fires that often occur are from July to November because this month is a dry month. By knowing the factors of forest fires, we can control them. Therefore, what can be done is by controlling the fuel which can be done by isolating the fuel, namely the fire break. This study aims to determine howto manage fuel  through the firebreak method at the SPFR Sisimeni Sanam. Methods of data collection using direct interview techniques, field documentation and library literature.  The results showed that the fuel management at SPFR Sisimeni Sanam used the yellow line manual firebreak method with a distance of 3 meters in each sample plots. This has not been effectively implemented in KHDTK Sisimeni Sanam because the fires in this area were mostly due to spot fire.